Letramento estatístico: construção e leitura de tabelas e gráficos a partir de atividades com alunos do Ensino Médio - Silva, Regina Matias da (2022)
The purpose of this work is to identify the elements of statistical literacy from a didactic sequence with high school students through activities that deal with the construction and reading of tables and graphs. We present as a theoretical reference theTheories of Didactic Situations (TSD) and Statistical Literacy and Exploratory Data Analysis. The activities were applied in six meetings, which consisted of a questionnaire that the students answered, using the google forms platform, from which we created a database, which was used for all activities involving the classification of statistical variables, construction and interpretation of tables and graphs. The activities showed that the mobilization of statistical knowledge, and the exploration of data analysis were partially satisfactory, showing that it is necessary to continue the contents, involving a broad preparation of these students, with a critical positioning in fact that can favor statistical literacy